(untitled) (Universal International Scientific Journal, 2026)
. This article examines the issues of ensuring mental health in the process of training highly qualified personnel in higher education institutions in the context of globalization. The study analyzes stress factors, adaptation processes, pedagogical and psychological support systems in students. At the same time, the impact of innovative approaches and the use of modern technologies on mental health and the educational process is studied. The results of the study show that the introduction of pedagogical and psychological innovations, the creation of a supportive environment, and stress-reducing programs help strengthen the psychological stability of students and increase the effectiveness of the educational process [1][2].